2009
DOI: 10.1002/cncr.24193
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the expression of vascular endothelial growth factors A, B, C, and D and their receptors R1, R2, and R3 in patients with nonsmall cell lung cancer

Abstract: BACKGROUND:Lung cancer is the leading cause of cancer death in the world. The objective of this study was to investigate the expression of vascular endothelial growth factors (VEGFs) and their receptors (VEGFRs) in patients with nonsmall cell lung cancer (NSCLC) and its correlation with the prognosis for patients with lung cancer.METHODS:The expression status of VEGFs and VEGFRs was examined in 48 nonconsecutive specimens of primary lung cancer by immunohistochemistry. Correlations between the expression of VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 54 publications
5
46
0
1
Order By: Relevance
“…In particular, it has been demonstrated that FLNA physically interacts with HIF-1a (Zhenga et al 2014), that regulates angiogenesis through upregulation of vascular endothelial growth factor (VEGF) (Uramoto et al 2010, Berardi et al 2011, Semenza 2012. Whereas VEGF-driven angiogenesis may play an important role in endocrine tumourigenesis and tumour progression (Hanahan et al 1996) and several in vitro studies suggested that SS analogues display potent antiangiogenic properties (Woltering et al 1991, Barrie et al 1993, Danesi & Del Tacca 1996, Kumar et al 2004, we showed that SST2 agonist reduced VEGF protein levels and release, but this inhibitory effect was totally abolished in the absence of FLNA.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In particular, it has been demonstrated that FLNA physically interacts with HIF-1a (Zhenga et al 2014), that regulates angiogenesis through upregulation of vascular endothelial growth factor (VEGF) (Uramoto et al 2010, Berardi et al 2011, Semenza 2012. Whereas VEGF-driven angiogenesis may play an important role in endocrine tumourigenesis and tumour progression (Hanahan et al 1996) and several in vitro studies suggested that SS analogues display potent antiangiogenic properties (Woltering et al 1991, Barrie et al 1993, Danesi & Del Tacca 1996, Kumar et al 2004, we showed that SST2 agonist reduced VEGF protein levels and release, but this inhibitory effect was totally abolished in the absence of FLNA.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, a positive relationship between FLNA and vascular endothelial growth factor (VEGF) was found in patients with lung cancer (Uramoto et al 2010), suggesting that FLNA is implicated in angiogenesis through links with VEGF. Interestingly, it has been demonstrated that VEGF pathway is overexpressed in neuroendocrine tumours (Ö berg et al 2013), this pathway being inhibited by somatostatin analogues (Villaume et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, VEGFR-1 is usually considered to function as a decoy receptor for VEGF, and it is not markedly phosphorylated upon VEGF binding (36). The prognostic role of VEGFR-1 in tumors has remained controversial (37,38). In the search for novel anticancer treatments, some of the new smallmolecule tyrosine kinase inhibitors are, however, designed also to inhibit VEGFR-1 (17).…”
Section: Discussionmentioning
confidence: 99%
“…Positive VEGF immunostaining independently predicts poor prognosis in gastric cancer patients. Strong VEGF staining showed a significant correlation with both short time of relapse and short survival in NSCLC [18]. Increased expression is also a prognostic marker in papillary thyroid carcinoma.…”
Section: Angiogenesis Markersmentioning
confidence: 95%